Pirólise termoquímica de pós da fibra de coco seco em um reator de cilindro rotativo para produção de bio-óleo - Figueiredo, Aneliése Lunguinho (2011)
This master thesis aims at developing a new methodology for thermochemical degradation of dry coconut fiber (dp = 0.25mm) using laboratory rotating cylinder reactor with the goal of producing bio-oil. The biomass was characterized by infrared spectroscopy with Fourier transform FTIR, thermogravimetric analysis TG, with evaluation of activation energy the in non-isothermal regime with heating rates of 5 and 10 °C/min, differential themogravimetric analysis DTG, sweeping electron microscopy SEM, higher heating value - HHV, immediate analysis such as evaluated all the amounts of its main constituents, i.e., lignin, cellulose and hemicelluloses. In the process, it was evaluated: reaction temperature (450, 500 and 550oC), carrier gas flow rate (50 and 100 cm³/min) and spin speed (20 and 25 Hz) to condensate the bio-oil. The feed rate of biomass (540 g/h), the rotation of the rotating cylinder (33.7 rpm) and reaction time (30 33 min) were constant. The phases obtained from the process of pyrolysis of dry coconut fiber were bio-oil, char and the gas phase non-condensed. A macroscopic mass balance was applied based on the weight of each phase to evaluate their yield. The highest yield of 20% was obtained from the following conditions: temperature of 500oC, inert gas flow of 100 cm³/min and spin speed of 20 Hz. In that condition, the yield in char was 24.3%, non-condensable gas phase was 37.6% and losses of approximately 22.6%. The following physicochemical properties: density, viscosity, pH, higher heating value, char content, FTIR and CHN analysis were evaluated. The sample obtained in the best operational condition was subjected to a qualitative chromatographic analysis aiming to know the constituents of the produced bio-oil, which were: phenol followed by sirigol, acetovanilona and vinyl guaiacol. The solid phase (char) was characterized through an immediate analysis (evaluation of moisture, volatiles, ashes and fixed carbon), higher heating value and FTIR. The non-condensing gas phase presented as main constituents CO2, CO and H2. The results were compared to the ones mentioned by the literature.